Seasonal Characteristics of Raindrop Size Distribution and Implication for Radar Rainfall Retrievals in Metro Manila, Philippines - Aragon, Larry Ger B. (Archīum Ateneo, 2024)
This study presents the first comprehensive analysis of the seasonal characteristics of raindrop size distribution (DSD) in Metro Manila, Philippines, using two years of measurements (2018–2020) from the PARSIVEL2 disdrometer. Seasonal properties of DSD for both stratiform and convective rain types were examined during the Southwest Monsoon (SWM; June–September), Northeast Monsoon (NEM; October–February), and pre-SWM or Transition period (March–May). Key findings reveal the dominance of small raindrops (<1 >mm) during the NEM period, while mid-sized (1–3 mm) to large raindrops (>3 mm) are more prevalent during the SWM and Transition periods. The study highlights notable seasonal differences in DSD at moderate rain rates (5–10 mm hr−1), indicating variations in microphysical processes between stratiform and convective rain. Furthermore, the microphysical properties of convective rain in Metro Manila are found to be influenced by both oceanic and continental convective processes based on their mass-weighted mean diameter and generalized intercept parameter for all the monsoon periods. The DSD-derived dual-polarimetric radar variables are also shown to vary with the monsoon periods. Rainfall estimates using the DSD-derived dual-polarimetric relations statistically outperformed the empirical rainfall retrieval equation currently used by operational weather radars in the Philippines. Additionally, the Gamma shape parameter found in this study aligns with existing rainfall retrieval algorithm assumptions in space-borne radars. This similarity, along with the derived microphysical relations, could provide potential improvements in rainfall retrievals of ground-based and space-borne radars in tropical coastal environments like Metro Manila.